Adverse events in hospitalised cancer patients: a comparison to a general hospital population. (2nd September 2017) - Haukland, Ellinor Christin; von Plessen, Christian; Nieder, Carsten; Vonen, Barthold
Abstract: Background: Patients with cancer are often treated by many healthcare providers, receive complex and potentially toxic treatments that can increase the risk for iatrogenic harm. The aim of this study is to investigate whether hospitalised cancer patients are at higher risk of adverse events (AEs) compared to a general hospital population. Material and methods: A total of 6720 patient records were retrospectively reviewed comparing AEs in hospitalised cancer patients to a general hospital population in Norway, using the IHI Global Trigger Tool method. Results: 24.2 percent of admissions for cancer patients had an AE compared to 17.4% of admissions of other patients ( p < .001, rr 1.39, 95% CI 1.19–1.62). However, cancer patients did not have a higher rate of AEs per 1000 patient days compared to other patients, 37.1 vs. 36.0 ( p = .65, rr 0.94, 95% CI 0.90–1.18). No particular cancer category is at higher risk. The rate of AEs increases by 1.05 times for each day spent in hospital. For every year increase in age, the risk for AEs increases by 1.3%. Cancer patients more often have hospital-acquired infections, other surgical complications and AEs related to medications. Conclusions: Because of higher age, longer length of stay and surgical treatment, hospitalised cancer patients experience AEs more often than other patients.